Sostenibilidad para los acueductos comunales en Costa Rica : desafíos pendientes en la gobernabilidad hídrica - Ingo Gentes; Róger Madrigal (VertigO)
Community water and sanitation bodies called ASADAS in Costa Rica provide a large part of water to rural population. These bodies claim for enhanced legal competencies and financial resources in order to improve distribution of water, to ensure protection of water aquifers, to build capacities among their members and to foment a broad environmental education among water users. The State confronts the challenge to fulfill these demands through institutional decentralization and a greater form of autonomy, though without renouncing to ensure an adequate access to sufficient and potable water resources.